A simple approach for the force control of bilateral teleoperated manipulators with variable time delays. (September 2020) - Hernández-Ortiz, Óscar; Arteaga-Pérez, Marco A.
Abstract: Local–remote teleoperated systems made up of robot manipulators have a large variety of applications, e. g. performing tasks in dangerous or inaccessible environments. They must provide the operator with the feeling of being in the remote environment and the ability of interacting with it. This objective is affected when time varying delays are present in the communication channel. In this work a control scheme for this kind of systems is proposed. It is shown that the local robot can be moved by the operator causing a (delayed) trajectory tracking in the remote manipulator. Should the later get in touch with the environment, the operator has some degree of delayed kinematic correspondence while the remote robot applies a force on the constraint surface tracking the (delayed) force commanded by the operator. The stability analysis is carried out under the assumptions that human and environment forces as well as their corresponding derivatives are bounded. Experimental results are provided to validate the proposed scheme, delivering a good performance both with rigid and elastic surfaces.